Assessment of the Effect of Rosemary on Tomato Preservation. - Nanyanzi,Teopista (Kabale University, 2024)
Despite the nutritional and economic importance of tomatoes, significant post-harvest losses persist, exacerbated by concerns over synthetic chemical preservatives' environmental and health impacts. Thus, there is a pressing need for sustainable and cost-effective preservation methods, such as the adoption of rosemary extract, which offers safer alternatives capable of extending the shelf life of tomatoes, especially in resource-limited settings. This study investigated the efficacy of rosemary extract in preserving tomatoes, aiming to assess its impact and evaluate varying concentrations on tomato shelf life. Fresh tomatoes were randomly sourced from local markets, and crude extracts were prepared from rosemary leaves using cold maceration. The experiment involved immersing tomato fruits in rosemary extract solutions at concentrations of 25%, 50%, 75%, and 100% w/v, while control fruits received treatment with sterile distilled water. Shelf life was evaluated based on visual appearance, spoilage occurrence, and physiological changes such as pH levels, weight loss, and titratable acidity. Results demonstrated that increasing concentrations of rosemary extract corresponded to prolonged shelf life, with tomatoes treated with 100% w/v rosemary extract exhibiting the longest preservation period of 22 ± 5 days. Treated tomatoes maintained stable pH levels, experienced reduced weight loss rates, and showed acceptable titratable acidity compared to untreated controls. These findings indicate that rosemary extract effectively preserves tomato quality by inhibiting microbial growth and oxidative deterioration. The study recommends further exploration to optimize rosemary extract formulations, facilitate industry adoption, and address regulatory considerations to promote its use as a sustainable solution for food preservation.